Stroke Severity Affects Timing: Time From Stroke Code Activation to Initial Imaging is Longer in Patients With Milder Strokes. Issue 3 (May 2018) - Kwei, Kimberly T.; Liang, John; Wilson, Natalie; Tuhrim, Stanley; Dhamoon, Mandip
Abstract : Optimizing the time it takes to get a potential stroke patient to imaging is essential in a rapid stroke response. At our hospital, door-to-imaging time is comprised of 2 time periods: the time before a stroke is recognized, followed by the period after the stroke code is called during which the stroke team assesses and brings the patient to the computed tomography scanner. To control for delays due to triage, we isolated the time period after a potential stroke has been recognized, as few studies have examined the biases of stroke code responders. This "code-to-imaging time" (CIT) encompassed the time from stroke code activation to initial imaging, and we hypothesized that perception of stroke severity would affect how quickly stroke code responders act. In consecutively admitted ischemic stroke patients at The Mount Sinai Hospital emergency department, we tested associations between National Institutes of Health Stroke Scale scores (NIHSS), continuously and at different cutoffs, and CIT using spline regression, t tests for univariate analysis, and multivariable linear regression adjusting for age, sex, and race/ethnicity. In our study population, mean CIT was 26 minutes, and mean presentation NIHSS was 8. In univariate and multivariate analyses comparing CIT between mild and severe strokes, stroke scale scores <4 were associated with longer response times. Milder strokes are associated with a longer CIT with a threshold effect at a NIHSS of 4.